Transneuronal retrograde degeneration of retinal ganglion cells after damage to striate cortex in macaque monkeys: selective loss of P beta cells. - Cowey, A; Stoerig, P; Perry, V (1989)
We examined the retinae of two monkeys whose left striate cortex had been removed eight years previously and compared the transneuronally degenerated hemiretina of each eye with the normal hemiretina, and with the retinae of normal monkeys. All retinae were prepared as whole mounts. One from each pair was stained with Cresyl Violet; the other was reacted for horseradish peroxidase two days after placing pellets of the enzyme in the optic nerve. Measurements of ganglion cell density in the Nissl-stained retina of the contralateral right eye showed that approximately 80% of retinal ganglion cells were missing in the central 30 degrees of the degenerated hemiretinae. More peripherally the percentage loss was less extensive. Measurements of cell soma size and dendritic field size of peroxidase-labelled classified surviving cells in the degenerated temporal hemiretina of the ipsilateral eye showed them to be morphologically normal. In comparison with the normal hemiretina, however, the mean soma size at three selected eccentricities was larger than normal, suggesting selective loss of smaller ganglion cells. Classification of peroxidase-labelled ganglion cells in the normal and degenerated hemiretinae revealed that the population of P beta cells was reduced by as much as 85% in the degenerated region. There was comparable change in the density of P alpha or P gamma cells. The degeneration of the great majority of P beta cells, which are believed to be the morphological substrate of ganglion cells with small and colour-opponent receptive fields, must set limits on the visual sensitivity and discrimination that survive damage to striate cortex.